GENDER INEQUALITY AND MORAL VALUE IN "WONDER WOMAN" BY PATTY JENKINS - Ayu Yuliani Eddy (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: The title of this thesis is “Gender Inequality and Moral Value in “Wonder Woman” by Patty Jenkins”. The study was conducted in August 2019. The objective of  this research paper was to found out the gender inequality and moral value of this movie. The research method was the qualitative. The instrument of this research were covered the list of the question designed based on the elements of the movie. The data was collected by watching the movie and reading the script movie,  identifying, classifying, and analyzing based on gender inequality and moral value. 1). The result of this research showed the Gender Inequality has highest percentage of the Gender Equality. The draw of Gender conclusion that the Gender Inequality is 33,45% and Gender Equality is 21,00%. 2). The moral value are justice 17,41%, honesty 33,45%, bravery 17,10%, responsibility 30,89%, and beneficence 31,11%. The beneficial input of analyzing the movie is that movie can be used as the advice for teacher of English can make students have positive character. Keywords: Gender Inequality; Moral Value; Movie